COMPARATIVE EVALUATION OF HARD AND SOFT TISSUE CHANGES AROUND IMMEDIATELY LOADED SHORT AND LONG DENTAL IMPLANTS: AN IN VIVO STUDY (Journal of Pharmaceutical Negative Results, 2022)
Background: Placing a dental implant in the resorbed alveolar ridge are always require complex implant surgeries. The hypothesis was that short implant could improve the implant success rate which is very conservative and efficient treatment modalities.Purpose: The purpose of the present study was to evaluate the hard and soft tissue changes around immediately loaded short and long dental implant.Material & Methods: A total of 15 patients were selected with 2 partially edentulous space and one short and one conventional implant was placed with immediate loading protocol. Then they were divided into two groups one immediately loaded short implant and second is immediately loaded long implants, hard and soft tissues changes were evaluated on day of implant placement and 1st month, 2nd months and 4th months.Results: The mean score value of marginal bone loss, plaque accumulation, probing depth and sulcular bleeding were seen to be more in long implant as compared to the short implant. The difference between them was deemed to be statistically insignificant (p<0.05)Conclusion: There was no significant difference recorded around immediately loaded short and conventional implant in survival rate. So, short implants could be used as an alternative for complex implant surgery in deficient ridges.